Spore levels in bulk tank organic raw milk and whole milk powder are reduced by udder hair singeing - Zoe D. Wasserlauf-Pepper; Rachel L. Weachock; Christina M. Geary; Martin Wiedmann; Nicole H. Martin (JDS Communications)
Routine removal of udder hair through singeing or clipping is a farm management practice that is often used with the intention of reducing SCC and mastitis caused by environmental pathogens. Udder hair removal was also recently identified as a factor of importance for the level of bacterial spores in certified organic bulk tank raw milk. Sporeforming bacteria form resistant endospores, or spores, that allow the organisms to survive harsh environmental conditions, including high temperatures, low moisture, exposure to chemicals, and other conditions that would otherwise be lethal to the vegetative cell. Due to this resistance, spores that are present in raw milk can survive processing hurdles used in dairy product manufacturing, germinate into vegetative cells, and ultimately cause spoilage and quality deterioration in dairy products including fluid milk, cheese, and products using dairy powders as ingredients. Therefore, the aim of this study was to determine if udder hair removal through singeing reduces the concentration of bacterial spores in certified organic bulk tank raw milk. Four organic dairy farms that had not routinely removed udder hair were recruited, and bulk tank samples were collected before and after a singeing intervention on all lactating dairy cows contributing to the bulk tank. Raw milk samples, as well as whole milk powder manufactured from the raw milk collected before and after the intervention, were assessed for different groups of dairy relevant bacterial spores. A numerical reduction from before to after intervention was observed in the mean raw milk mesophilic spore count, thermophilic spore count, and butyric acid bacteria most probable number, whereas a numerical increase was observed in the mean raw milk total bacteria count and psychrotolerant spore most probable number, although none of these changes were significant. The mean mesophilic spore count and thermophilic spore count in whole milk powder manufactured from pre- and post-intervention raw milk was, however, significantly reduced from 2.46 to 1.58 log10 cfu/g and 1.44 to 1.22 log10 cfu/g, respectively. The results of our study indicate that udder hair removal may aid in reducing key populations of spores found in organic raw milk and resulting dairy powders manufactured from that raw milk, although the small sample size in our study likely affected the significance of our results. Future studies should further investigate the role of udder hair removal on a larger set of organic farms, as well as the downstream impact on spore levels in other manufactured dairy products.